A Harsh Environment Wireless Pressure Sensing Solution Utilizing High Temperature Electronics - Jie Yang (Sensors, 2013)
Pressure measurement under harsh environments, especially at high temperatures, is of great interest to many industries. The applicability of current pressure sensing technologies in extreme environments is limited by the embedded electronics which cannot survive beyond 300 °C ambient temperature as of today. In this paper, a pressure signal processing and wireless transmission module based on the cutting-edge Silicon Carbide (SiC) devices is designed and developed, for a commercial piezoresistive MEMS pressure sensor from Kulite Semiconductor Products, Inc. Equipped with this advanced high-temperature SiC electronics, not only the sensor head, but the entire pressure sensor suite is capable of operating at 450 °C. The addition of wireless functionality also makes the pressure sensor more flexible in harsh environments by eliminating the costly and fragile cable connections. The proposed approach was verified through prototype fabrication and high temperature bench testing from room temperature up to 450 °C. This novel high-temperature pressure sensing technology can be applied in real-time health monitoring of many systems involving harsh environments, such as military and commercial turbine engines.